การพัฒนากระบวนการเรียนการสอนตามแนวคิดการตั้งปัญหาและการคิดแบบฮิวริสติกส์ เพื่อส่งเสริมความสามารถในการแก้โจทย์ปัญหาคณิตศาสตร์ของนักเรียนระดับมัธยมศึกษาตอนต้น - วรพิน, กฤษฎา; เสวกงาม, วิชัย; ม้าคนอง, อัมพร (Journal of Education Studies, Chulalongkorn University, 2019)
This research aimed to develop and study the effectiveness of an instructional process based on problem posing and heuristics thinking approaches to enhance the mathematics problem solving ability of lower secondary school students. This research and development included a demonstration. The research operation was divided into two phases: phase 1 was to develop an instructional process based on the problem posing and heuristics thinking approach and phase 2 was to experiment with an instructional process. The sample group was composed of 80 secondary school students in Mathayom 3. The tool for data collection was a performance test in problem solving set 1 and set 2 which aimed to evaluate the effectiveness of the instructional process. The results of the research can be summarized as follows: 1) An instructional process based on the problem posing and heuristics thinking approach consisted of five steps which include posing a problem to connect with prior knowledge, representing a new concept, confronting the problem and understanding the problem, grouping for solving the problem, and concluding and extending the problem. 2) Students with this instructional method were capable of solving mathematical problems. The post-test demonstrated a higher result than the pre-test at a .05 level of significance. 3) Students with this instructional method were capable of solving mathematical problems at a greater rate than students with conventional instruction at a .05 level of significance.